Sensor database from digital plot Chiquimula, Guatemala - 2025 - Estrada Vargas, Oscar Hernan; Ramos Solorzano, Gresia Dalal; Lizarazo Torres, Miguel Angel; Jimenez Rodas, Daniel Ricardo (2026)
These are data collected from climate and soil sensors in the digital maize plot at San Carlos University, CUNORI, which primarily aim to provide crucial information about the conditions affecting crop development. This data enables farmers, researchers, and academics to better understand how digital technologies can improve the productivity and sustainability of agricultural systems. Methodology:The data is extracted from the nMetos weather station and soil probe device through the FieldClimate API